KEARIFAN LOKAL BERLADANG DALAM PERSPEKTIF FILOSOFI HIDUP DAN PEMENUHAN KEBUTUHAN SUKU DAYAK DI SINTANG - Mardawani, Mardawani; Suparno, Suparno; Suseka, Septa (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
This research is entitled "Ethnographic Study of Land Burning in the Perspective of Philosophy of Life and Meeting the Needs of the Dayak Tribe in Sintang Regency." The background of the existence of Indonesia as a country with a diversity of procedures and customs. This thing has implications for the way people live and fulfill their needs. In the modern era, the role of indigenous peoples has begun to shift, and the basic values that were once noble are fading. It is indicated by several phenomena, such as the diminishing value of role models and farming activities containing a philosophy of life that shifts to commercial activities. The research objective is to find the values of the philosophy of life and life in farming activities. The method used to carry out qualitative data analysis is in the form of an ethnographic study. Data collection tools include observation sheets, interview sheets, and study documentation. The research subject is the Dayak Tribe (cultivators) in Sintang Regency. It can be concluded: 1). The study of farming from the perspective of the philosophy of life and the fulfillment of the needs of the Dayak tribe in Sintang Regency is identical to farming life because, since the time of the ancestors, it has been carried out from generation to generation. Farming is not only to fulfill food needs; it also preserves the spiritual bond of the farmer's ritual with the land and his ancestors. 2). farming is local wisdom with values of life and philosophy of life for the Dayak tribe. The values of life and philosophy contained in farming the Dayak tribe in Sintang are a form of conservation religion in building human harmony with nature. 3). The Dayak tribe in Sintang Regency builds relationships between God and the environment related to farming activities through various stages of farming activities ranging from clearing land, planting, and maintaining to harvesting.Â Keywords: land burning, philosophy of life, fulfillment of needs, Dayak tribeÂ